Analysis of stress in steel and concrete in cfst push-out test samples = Analiza naprężeń w betonie i stali w elementach CFST poddanych badaniu push-out - Grzeszykowski, Bartosz; Szadkowska, Magdalena; Szmigiera, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the analysis of stress in steel and concrete in CFST composite elements subjected to push-out tests. Two analytical models of stress distribution are presented. The bond at the interface between steel and concrete in the initial phase of the push-out test is provided by the adhesion.
Keywords: composites; steel-concrete column; CFST; bond stress; adhesion; push-out test; elementy zespolone; element stalowo-betonowy; naprężenie przyczepności; adhezja; test push-out